The encyclopedia of the Spanish-American and Philippine-American wars a political, social, and military history - Tucker, Spencer 1937- (Gale virtual reference library, 2009)
Provides a comprehensive overview of the wars that saw the United States emerge as a world power; one that had immense implications for America, especially in Latin America and Asia.